Disappearing Polymorphs in Metal–Organic Framework Chemistry: Unexpected Stabilization of a Layered Polymorph over an Interpenetrated Three‐Dimensional Structure in Mercury Imidazolate. Issue 8 (16th January 2020) - Speight, Isaiah R.; Huskić, Igor; Arhangelskis, Mihails; Titi, Hatem M.; Stein, Robin S.; Hanusa, Timothy P.; Friščić, Tomislav
Abstract: The "disappearing polymorph" phenomenon is well established in organic solids, and has had a profound effect in pharmaceutical materials science. The first example of this effect in metal‐containing systems in general, and in coordination‐network solids in particular, is here reported. Specifically, attempts to mechanochemically synthesize a known interpenetrated diamondoid ( dia ) mercury(II) imidazolate metal–organic framework (MOF) yielded a novel, more stable polymorph based on square‐grid ( sql ) layers. Simultaneously, the dia ‐form was found to be highly elusive, observed only as a short‐lived intermediate in monitoring solvent‐free synthesis and not at all from solution. The destabilization of a dense dia ‐framework relative to a lower dimensionality one is in contrast to the behavior of other imidazolate MOFs, with periodic density functional theory (DFT) calculations showing that it arises from weak interactions, including structure‐stabilizing agostic C−H⋅⋅⋅Hg contacts. While providing a new link between MOFs and crystal engineering of organic solids, these findings highlight a possible role for agostic interactions in directing topology and stability of MOF polymorphs. Abstract : Mechanochemical synthesis of mercury(II) imidazolate reveals a layered framework that is, based on reaction monitoring and theoretical calculations, more stable than the previously reported interpenetrated polymorph. The stabilization highlights a role for weak agostic contacts in MOF stability, whereas the inability to reproduce the previously known form represents the first example of the disappearing polymorph phenomenon in coordination chemistry.